An Application of Cuckoo Search Algorithm for Solving Combined Economic and Emission Dispatch Problem - M. H., Sulaiman; Zuriani, Mustaffa; Nor Rul Hasma, Abdullah (2015)
This paper presents the application of Cuckoo Search Algorithm (CSA) in solving the combined economic and emission (CEED) dispatch problem. As been known, CEED can be formulated as a multi-objective optimization problem which is involving two objectives that conflicting each other. The objective is to find the tradeoff between minimizing the costs of fuel as well as minimizing the emission levels simultaneously while satisfying all the constraints. In this paper, this bi-objective function is transformed into a single objective function by introducing the price penalty and weighting factors. In order to show the effectiveness of CSA in solving CEED, two test systems are used: 6-units and 40-units generator systems. The comparison with other recent techniques is also given in this paper.